Малоизвестные виды подсемейства Medeterinae (Diptera, Dolichopodidae) фауны СССР - Негробов, О.П. (Вестник зоологии, 1971)
As a result of studying the fauna of Medeterinae subfamily new and little known
species of Medetera genus were found in the USSR: M. abstrusa Thuneb. , M. belgica
P а г., M. breviseta P а г., M. flavipes M g., M. impigra Coll. , M. jugalis Co 11., M.
longicauda Beck., M. striata Par.
The status of M. striata Par . species is established.